Determining Travel Time and Fastest Route Using Dijkstra Algorithm and Google Map - Suardinata Suardinata; Rusdisal Rusmi; Muhammad Amrin Lubis (Sistemasi: Jurnal Sistem Informasi, 2022)
Dijkstra's algorithm is commonly used to determine the shortest route connecting a point as a starting node to another which acts as the end node. In this study, the UNP student dormitory acted as the starting node, while the library which is frequently visited by students was sampled from the campus as the end node. Due to the fact that students generally live around campus and move on foot, an alternative route is needed to determine the fastest travel time. Therefore, this study aims to determine the route with the fastest travel time from the start to the end of nodes using the Dijkstra algorithm, in comparison with the route displayed by Google Map. Data were obtained from Google Map, which showed the availability of many routes with the possibility of students taking the fastest travel time. The result showed that the fastest route using the Dijkstra algorithm and Google Map were 14 and 3 alternatives at 15 and 21 minutes intervals. Based on these data, it is concluded that the travel time through the fastest route obtained using the Dijkstra algorithm was 6 minutes faster than data found in the Google Map.